ICT in Participatory Development of Teaching/Learning English as a Global Language in Nigeria: A Discourse - Queen Ugochinyere Njamanze (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2011)
Information Communication Technology (ICT) has become a major issue in many language discourses today. English language is widely used in communication, education and diverse human endeavors. In Nigeria, it is the official language as well as the language of everyday use. Based on this, there is need to sustain and attain global proficiency and mastery. Being one of the parameters for measuring a nation's development, this paper emphasizes the need for the inclusion of ICT as a partner for national development. The researcher examines English as a global language, the place of ICT in Nigeria and the various technological applications and programs used in carrying out this growth, and development of English Language teaching/learning in Nigeria. The paper concludes by reaffirming the need for increased digital access and awareness in Nigeria